2016
DOI: 10.1038/ncomms10664
|View full text |Cite
|
Sign up to set email alerts
|

Differential Rac1 signalling by guanine nucleotide exchange factors implicates FLII in regulating Rac1-driven cell migration

Abstract: The small GTPase Rac1 has been implicated in the formation and dissemination of tumours. Upon activation by guanine nucleotide exchange factors (GEFs), Rac1 associates with a variety of proteins in the cell thereby regulating various functions, including cell migration. However, activation of Rac1 can lead to opposing migratory phenotypes raising the possibility of exacerbating tumour progression when targeting Rac1 in a clinical setting. This calls for the identification of factors that influence Rac1-driven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
108
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(121 citation statements)
references
References 70 publications
(97 reference statements)
8
108
0
Order By: Relevance
“…Second harmonic generation (SHG) imaging (31) and polarized light microscopy of picrosirius red staining (32, 33) of contracted collagen matrices revealed a reduction in fibrillar collagen coverage upon ROCK inhibition compared to control (Fig. 1, B to D, and fig.…”
Section: Resultsmentioning
confidence: 97%
“…Second harmonic generation (SHG) imaging (31) and polarized light microscopy of picrosirius red staining (32, 33) of contracted collagen matrices revealed a reduction in fibrillar collagen coverage upon ROCK inhibition compared to control (Fig. 1, B to D, and fig.…”
Section: Resultsmentioning
confidence: 97%
“…This leads to the remodelling of peripheral actin filaments in endothelial cells 89 . Another example is the RAC GEF P-REX1, which brings RAC1 together with its target FLI1 (friend leukaemia integration 1 transcription factor) to stimulate cell migration 90 . Similarly, DOCK1 is recruited to sites of developing cell-cell contacts by ELMO2 (engulfment and cell motility protein 2) 91 .…”
Section: Wave Regulatory Complexmentioning
confidence: 99%
“…It has been shown that activation of Rac1 is regulated by guanine nucleotide exchange factors (GEFs) [26]. To determine which exchange factors activate Rac1 downstream of autocrine VEGF and IL-8, we first investigated the endogenous expression of candidate Rac1 GEFs (Vav2, Tiam1, β-PIX, Sos-1 and DOCK180) in HUVECs.…”
Section: Resultsmentioning
confidence: 99%
“…Like all GTPases, the Rac1 is under tight spatial control, which is mediated by guanine nucleotide exchange factors (GEFs) and GTPase-activating proteins (GAPs) that catalyse GTP exchange and hydrolysis, respectively [23]. Specific GEF allows Rac1 to be activated in specific signal transduction pathways and coordinate more elaborate responses to specific demands at localized cellular sites [26, 42]. In this study, we identified the exchange factor Vav2 as mediating autocrine VEGF and IL-8 signaling to Rac1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation